1989
DOI: 10.1103/physrevb.39.10470
|View full text |Cite
|
Sign up to set email alerts
|

Optical activity of theEL2metastable state under hydrostatic pressure

Abstract: %e present experimental results showing that at hydrostatic pressure exceeding approximately 0.3 GPa the EL2 metastable state becomes optically active in both n-type and semi-insulating GaAs, and the pressure-induced optical recovery (PIOR) can be easily observed. PIOR is practically full and extremely efficient (with an efficiency comparable with that of the photoquenching process). The proper choice of the energy of the illuminating light allows reversible cycles of photoquenching and subsequent optical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Thus it remains the third possibility that the effect is caused by a change of a charge state of the metastable configuration due to trapping of the photoexcited electron. Such explanation is in agreement with recent findings of Baj et al [13] who showed that EL2 in the metastable configuration is an electron trap.…”
supporting
confidence: 82%
“…Thus it remains the third possibility that the effect is caused by a change of a charge state of the metastable configuration due to trapping of the photoexcited electron. Such explanation is in agreement with recent findings of Baj et al [13] who showed that EL2 in the metastable configuration is an electron trap.…”
supporting
confidence: 82%
“…the acceptor-like ( E L 2 * )°/ -l e v e l e n t e r s t h e e n e r g y g a p u n d e r p r e s s u r e . W e p r o p o s e t h a t i n n -G a A s t h e ΕL2 thermal recovery takes always place via the (ΕL2') state.PACS numbers:71.55.Eq, 78.50.GeOur recent experimental results showed that under pressure of p > 0.3 GPa the metastable configuration of the EL2 defect in GaAs became optically sensitive and a very efficient pure optical recovery process was observed [1]. We suggested that these facts could be related to the acceptor-like level of the metastable EL2 -(EL2*)0/ -, entering the gap under pressure.…”
mentioning
confidence: 93%
“…Our recent experimental results showed that under pressure of p > 0.3 GPa the metastable configuration of the EL2 defect in GaAs became optically sensitive and a very efficient pure optical recovery process was observed [1]. We suggested that these facts could be related to the acceptor-like level of the metastable EL2 -(EL2*)0/ -, entering the gap under pressure.…”
mentioning
confidence: 97%
“…Some of excited electrons were captured by shallow donors which was directly shown by a magnetooptical experiment [4]. A long lifetime of optically excited electrons in the conduction band and on shallow donors is caused by a configurational barrier for capturing an electron on the EL2 [5] and a spatial separation of an excited electron from its parental centre [6]. A sufficiently high electric field caused impact ionization of electrons bound on shallow donors and in wells of the fluctuating potential at the bottom of the conduction band.…”
Section: Introductionmentioning
confidence: 99%